Metabolic response of human osteoarthritic cartilage to biochemically characterized collagen hydrolysates - Schadow, Saskia; Simons, Viktor S.; Lochnit, Guenter; Kordelle, Jens; Gazova, Zuzana; Siebert, Hans-Christian; Steinmeyer, Juergen; Justus Liebig University Giessen (My University, 2017)
The most frequent disease of the locomotor system is osteoarthritis (OA), which, as a chronic joint disease, might benefit more from nutrition than acute illnesses. Collagen hydrolysates (CHs) are peptidic mixtures that are often used as nutraceuticals for OA. Three CHs were characterized biochemically and pharmacologically. Our biophysical (MALDI-TOF-MS, NMR, AFM) and fluorescence assays revealed marked differences between CHs of fish (Peptan® F 5000, Peptan® F 2000) and porcine (Mobiforte®) origin with respect to the total number of peptides and common peptides between them. Using a novel dual radiolabeling procedure, no CH modulated collagen biosynthesis in human knee cartilage explants. Peptan® F 2000 enhanced the activities of the aggrecanase ADMATS4 and ADMATS5 in vitro without loss of proteoglycan from cartilage explants; the opposite effect was observed with Mobiforte®. Interleukin (IL)-6, matrix metalloproteinase (MMP)-1, -3 and -13 levels were elevated in explants that were treated with Mobiforte® and Peptan® F 5000, but not with Peptan® F 2000. In conclusion, the heterogeneous peptide composition and disparate pharmacological effects between CHs suggest that the effect of a CH preparation cannot be extrapolated to other formulations. Thus, the declaration of a CH as a safe and effective nutraceutical requires a thorough examination of its pleiotropic effects.
Keywords: collagen hydrolysate; osteoarthritis; cartilage; ADAMTS; MMP; ddc:610